Strengthening Civil Servants' Digital Talent Through Peer Learning: Building Digital Champions as the Foundation of Agile Government in North Pontianak District, Pontianak City, West Kalimantan Province - Maris Gunawan Rukmana; Tunggul Prasodjo; Febby Suryatrisna; Lalu Budiman; Teguh Adiguna; Valencia Ovary Widyatamaka Saraswati (Manunggal Halim Jaya, 2026)
This Community Service Program (PKM) aimed to enhance the digital talent capacity of 22 civil servants at the North Pontianak District Office through a peer learning scheme based on digital champions as a mechanism for internalizing agile government principles, thereby promoting faster, more accurate, adaptive, and consistent public services. The program was conducted over three days (22–24 April 2026) using three sequential methods: (1) a Participatory Digital Talent Assessment to identify digital talent gaps and select potential digital champions; (2) an Experiential Learning Workshop based on Kolb’s learning cycle to internalize the five most relevant agile government principles; and (3) a Structured Peer Learning scheme involving seven selected digital champions who mentored their colleagues through real workplace tasks. The assessment results indicated that 63.64% of participants were classified as proficient, 9.09% as developing, and 27.27% as beginners. A comparison of pre-test and post-test results revealed an increase of 11.36 percentage points in digital technical competencies and 4.45 percentage points in the understanding of agile government principles. The key outcomes of the program included the formal establishment of a digital peer learning mechanism as a permanent internal learning system through the North Pontianak District Head’s Commitment Charter, as well as the creation of an internal communication group connecting digital champions and civil servants via the WhatsApp platform. The findings demonstrate that the PKM program was effective in reducing the digital talent gap among civil servants, fostering the internalization of agile government values, and establishing an institutional foundation for the advancement of smart government at the local government level, particularly within district government institutions.